Efforts to Increase Students' Understanding of Islamic Teachings Through Extracurricular Tahfidz Activities in Schools Based on Islamic Boarding Schools - Septantiningtyas, Niken; Fajri, Zaenol; Daraini, Saadatud (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Islamic religious teachings have long been thoroughly studied in Islamic boarding schools. Nevertheless, issues that arise as the times change lead to less than ideal-Islamic religious instruction in Islamic boarding schools. One of the issues is boring instruction, namely the lecture style that is constantly used, which makes pupils disinterested and less able to comprehend Islamic religious doctrine. Innovation in Islamic religious education must continuously be enhanced because many students are drowsy during class, particularly in Islamic boarding schools. Other educational institutions also assist in teaching Islam. Methodology: This study seeks to increase students' understanding of Islamic religious doctrines through extracurricular activities in Islamic boarding schools. Because this study examines a single case and gathers data via observations, interviews, and document analysis, it employs a descriptive qualitative technique with a case study design. Main Findings: The study's findings demonstrate that Islamic boarding schools can use extracurricular activities to teach Islam. Following the completion of learning activities, student learning outcome reports show the study's results when it is implemented methodically and taught in a way that meets the needs of the students. Novelty/Originality of this study: The study concludes that extracurricular activities at Islamic boarding schools are a good way to increase students' understanding of Islamic beliefs. The novelty of this approach and the focus of this study enrich the literature on Islamic education and inspire educational policymakers to design religious programs that have a real impact.